Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
(5x + -3)(x + -2)(2x + 5) + -1(3x + -2)(2x + -5)(x + -4) = 0

Reorder the terms:
(-3 + 5x)(x + -2)(2x + 5) + -1(3x + -2)(2x + -5)(x + -4) = 0

Reorder the terms:
(-3 + 5x)(-2 + x)(2x + 5) + -1(3x + -2)(2x + -5)(x + -4) = 0

Reorder the terms:
(-3 + 5x)(-2 + x)(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0

Multiply (-3 + 5x) * (-2 + x)
(-3(-2 + x) + 5x * (-2 + x))(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0
((-2 * -3 + x * -3) + 5x * (-2 + x))(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0
((6 + -3x) + 5x * (-2 + x))(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0
(6 + -3x + (-2 * 5x + x * 5x))(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0
(6 + -3x + (-10x + 5x2))(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0

Combine like terms: -3x + -10x = -13x
(6 + -13x + 5x2)(5 + 2x) + -1(3x + -2)(2x + -5)(x + -4) = 0

Multiply (6 + -13x + 5x2) * (5 + 2x)
(6(5 + 2x) + -13x * (5 + 2x) + 5x2 * (5 + 2x)) + -1(3x + -2)(2x + -5)(x + -4) = 0
((5 * 6 + 2x * 6) + -13x * (5 + 2x) + 5x2 * (5 + 2x)) + -1(3x + -2)(2x + -5)(x + -4) = 0
((30 + 12x) + -13x * (5 + 2x) + 5x2 * (5 + 2x)) + -1(3x + -2)(2x + -5)(x + -4) = 0
(30 + 12x + (5 * -13x + 2x * -13x) + 5x2 * (5 + 2x)) + -1(3x + -2)(2x + -5)(x + -4) = 0
(30 + 12x + (-65x + -26x2) + 5x2 * (5 + 2x)) + -1(3x + -2)(2x + -5)(x + -4) = 0
(30 + 12x + -65x + -26x2 + (5 * 5x2 + 2x * 5x2)) + -1(3x + -2)(2x + -5)(x + -4) = 0
(30 + 12x + -65x + -26x2 + (25x2 + 10x3)) + -1(3x + -2)(2x + -5)(x + -4) = 0

Combine like terms: 12x + -65x = -53x
(30 + -53x + -26x2 + 25x2 + 10x3) + -1(3x + -2)(2x + -5)(x + -4) = 0

Combine like terms: -26x2 + 25x2 = -1x2
(30 + -53x + -1x2 + 10x3) + -1(3x + -2)(2x + -5)(x + -4) = 0

Reorder the terms:
30 + -53x + -1x2 + 10x3 + -1(-2 + 3x)(2x + -5)(x + -4) = 0

Reorder the terms:
30 + -53x + -1x2 + 10x3 + -1(-2 + 3x)(-5 + 2x)(x + -4) = 0

Reorder the terms:
30 + -53x + -1x2 + 10x3 + -1(-2 + 3x)(-5 + 2x)(-4 + x) = 0

Multiply (-2 + 3x) * (-5 + 2x)
30 + -53x + -1x2 + 10x3 + -1(-2(-5 + 2x) + 3x * (-5 + 2x))(-4 + x) = 0
30 + -53x + -1x2 + 10x3 + -1((-5 * -2 + 2x * -2) + 3x * (-5 + 2x))(-4 + x) = 0
30 + -53x + -1x2 + 10x3 + -1((10 + -4x) + 3x * (-5 + 2x))(-4 + x) = 0
30 + -53x + -1x2 + 10x3 + -1(10 + -4x + (-5 * 3x + 2x * 3x))(-4 + x) = 0
30 + -53x + -1x2 + 10x3 + -1(10 + -4x + (-15x + 6x2))(-4 + x) = 0

Combine like terms: -4x + -15x = -19x
30 + -53x + -1x2 + 10x3 + -1(10 + -19x + 6x2)(-4 + x) = 0

Multiply (10 + -19x + 6x2) * (-4 + x)
30 + -53x + -1x2 + 10x3 + -1(10(-4 + x) + -19x * (-4 + x) + 6x2 * (-4 + x)) = 0
30 + -53x + -1x2 + 10x3 + -1((-4 * 10 + x * 10) + -19x * (-4 + x) + 6x2 * (-4 + x)) = 0
30 + -53x + -1x2 + 10x3 + -1((-40 + 10x) + -19x * (-4 + x) + 6x2 * (-4 + x)) = 0
30 + -53x + -1x2 + 10x3 + -1(-40 + 10x + (-4 * -19x + x * -19x) + 6x2 * (-4 + x)) = 0
30 + -53x + -1x2 + 10x3 + -1(-40 + 10x + (76x + -19x2) + 6x2 * (-4 + x)) = 0
30 + -53x + -1x2 + 10x3 + -1(-40 + 10x + 76x + -19x2 + (-4 * 6x2 + x * 6x2)) = 0
30 + -53x + -1x2 + 10x3 + -1(-40 + 10x + 76x + -19x2 + (-24x2 + 6x3)) = 0

Combine like terms: 10x + 76x = 86x
30 + -53x + -1x2 + 10x3 + -1(-40 + 86x + -19x2 + -24x2 + 6x3) = 0

Combine like terms: -19x2 + -24x2 = -43x2
30 + -53x + -1x2 + 10x3 + -1(-40 + 86x + -43x2 + 6x3) = 0
30 + -53x + -1x2 + 10x3 + (-40 * -1 + 86x * -1 + -43x2 * -1 + 6x3 * -1) = 0
30 + -53x + -1x2 + 10x3 + (40 + -86x + 43x2 + -6x3) = 0

Reorder the terms:
30 + 40 + -53x + -86x + -1x2 + 43x2 + 10x3 + -6x3 = 0

Combine like terms: 30 + 40 = 70
70 + -53x + -86x + -1x2 + 43x2 + 10x3 + -6x3 = 0

Combine like terms: -53x + -86x = -139x
70 + -139x + -1x2 + 43x2 + 10x3 + -6x3 = 0

Combine like terms: -1x2 + 43x2 = 42x2
70 + -139x + 42x2 + 10x3 + -6x3 = 0

Combine like terms: 10x3 + -6x3 = 4x3
70 + -139x + 42x2 + 4x3 = 0
Processing time: 2 ms. 53589214 equations since February 08, 2004.   Disclaimer

Equation Simplifying Calculator

Equation:
   
TIP: To solve equations, try the Equation Solving Calculator.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors